Developing English Vocabulary Reading Skills Using Phonics Teaching Method at Alounsavath School Luang Prabang District, Luang Prabang Province - PHOUTSAVATH, Pathana; KOUNLAXAY, Kalaphat; PANFONGPHET, Sipaseuth; BOUDSIT, Oudom (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Accurate pronunciation of English vocabulary is considered one of the most essential aspects of second language learning, as it serves as the foundation for the development of reading skills. Therefore, this study aimed to examine the level of students’ ability in pronouncing English words correctly through the use of the Phonics Method. The sample group consisted of 44 grade 5 students from Alounsavath Primary School, Luang Prabang District, Luang Prabang Province, during the academic year 2025–2026. The research tools included 7 instructional lessons and a reading pronunciation ability test composed of 7 subtests, each containing 5 items. The results found that 1) The students demonstrated a high level of ability in pronouncing English words after participating in the learning activities that applied the Phonics Method, Overall, their pronunciation ability was rated at a high level, with a mean score of ( = 3.06, SD) = 0.28; 2) When considering each aspect individually, it was found that the students demonstrated the highest level of ability in identifying the sounds in words, with a mean score ( = 3.38, SD = 0.27). The second highest level was in learning the letter information, with a mean score ( = 3.26, SD = 0.42). The aspect with the lowest mean score was blending, with a mean score ( = 2.75, SD =1.05); 3) When analyzing the results of the 7 subtests, the mean scores were as follows: Sub-test 1: ( = 2.81), Sub-test 2: ( = 2.91, SD =), Sub-test 3: ( = 3.00), Sub-test 4: ( = 2.86, SD =), Sub-test 5: ( = 3.22, SD =0.44), Sub-test 6: ( = 3.31, SD =) and Sub-test 7: ( = 3.37, SD =). These results indicate a steady improvement in students’ pronunciation ability across the 7 lessons, suggesting that the Phonics Method contributed positively to their learning progress. The study’s result demonstrate that students made noticeable progress in developing their ability to pronounce English words accurately.